How to understand what you don't believe: Metacognitive training prevents belief-biases in multiple text comprehension. (February 2021) - Abendroth, Johanna; Richter, Tobias
Abstract: Prior beliefs often bias the comprehension of multiple science-related texts such that belief-consistent texts are better comprehended compared to belief-inconsistent texts (text-belief consistency effect). Two experiments were conducted to investigate whether a metacognitive strategy training focusing on belief-biasing validation processes can reduce the text-belief consistency effect in multiple text comprehension. Participants in the control condition received the PQ4R training as a well-situated and effective reading skill training that increases receptive elaborative processing. In Experiment 1 ( n  = 39) and Experiment 2 ( n  = 53) participants receiving a metacognitive strategy training achieved a similar level of comprehension of belief-consistent and belief-inconsistent texts, whereas a text-belief consistency effect was found in the PQ4R condition. These results indicate that a training focusing on belief-biasing validation processes prepare readers for the challenges to comprehend belief-relevant multiple texts, whereas strategies that foster receptive processing of information are not sufficient in the context of controversially discussed topics. Highlights: Belief-consistent texts are better comprehended as belief-inconsistent texts. Such a bias reduces readers' ability to fully understand controversially issues. Assisting readers in comprehending multiple belief-relevant texts is important. A metacognitive training on belief-biasing validation can reduce the belief bias. A training on receptive processing of information is not sufficient.